The Effect of Work Environment and Compensation on Employee Performance - Ahmad Ivan Akmaluddin; Umar Khasan; Siti Nur Qomariyah (Benchmark, 2022)
This study aims to determine the effect of the working environment and compensation to employee performance at PT. Jombang Intermedia Press (Radar Jombang). The sample of this research is a permanent employee at PT. Jombang Intermedia Press (Radar Jombang) by 40 respondents. Methods of analyzing data used in this study include testing instrument, the classical assumption, t test, F test and multiple linear regression. The results of this study indicate that the Work Environment and Compensation positive and significant effect on the performance of employees at PT. Jombang Intermedia Press (Radar Jombang). Therefore, PT. Jombang Intermedia Press (Radar Jombang) should maintain and facilitate all the needs of physically and psychologically to support all forms of employees' work activities.